2014
DOI: 10.1016/j.crohns.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions, attitudes, and experiences about the management of mild-to-moderate ulcerative colitis

Abstract: The results suggest the importance of developing strategies to facilitate care on demand and remote care, and to investigate on effective and safe treatments to minimize the detriment to quality of life of patients. These strategies should guarantee fast care and, together with safe and effective treatments, optimize the management of UC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Qualitative analysis of data from these CE interviews disclosed the substantial emotional and physical burden of UC, as well as the impact on participants' lives. The significant symptomatic and HRQoL impacts of living with UC affected children in ways that clearly show homogeneity with previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. There was a high level of agreement between children and parents/caregivers regarding the presence or absence of symptoms.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Qualitative analysis of data from these CE interviews disclosed the substantial emotional and physical burden of UC, as well as the impact on participants' lives. The significant symptomatic and HRQoL impacts of living with UC affected children in ways that clearly show homogeneity with previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. There was a high level of agreement between children and parents/caregivers regarding the presence or absence of symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Previous qualitative research has primarily focused on adults, with most studies utilizing patients with mixed inflammatory bowel disease (IBD) etiologies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A failure in these studies to analyze data by specific Table 3 Frequency counts for agreement on presence/absence of a symptom/impact by the parent and child during dyad interviews condition, made it previously impossible to differentiate findings attributable to UC versus other IBD conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar change in priority was identified in group discussions with Spanish patients with UC. 15 Of note, physicians are typically more concerned about side effects in older patients. In contrast, younger patients placed more emphasis on avoiding side effects than older patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Casellas et al[ 16 ] showed that satisfaction with information was scored the lowest of the 6 rated domains and that lack of information was a constant complaint of patients over time, especially for those with mild to moderate conditions who were not mainly followed by gastroenterologists. [ 28 ] Some patients’ views of quality improvements in gastrointestinal diseases were directed at increasing access to patient organizations and groups, having consistency and coordination between GPs and hospital management,[ 29 ] improving knowledge of GPs on IBD,[ 28 , 30 ] and being more involved in defining disease-related concerns and prioritization of outcomes. [ 29 ] We also observed that communication within the healthcare network was not considered optimal.…”
Section: Discussionmentioning
confidence: 99%